1987
DOI: 10.1111/j.1467-9817.1987.tb00278.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of leisure‐time reading

Abstract: Pupils from middle-class homes devoted an average of 7.2 per cent of leisure time to reading. The relationship between home environment, attitude to reading and motivations for reading on the one hand and leisure-time reading on the other, was examined. The addition of these sets of variables to previously established correlates of leisure-time reading, achievement, sex, and library membership increased the proportion of variance accounted for in leisure-time reading by a significant amount (10.1 per cent). Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
1
9

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 24 publications
3
59
1
9
Order By: Relevance
“…Examining the relationship between parents and children's reading backgrounds and habits, the parental factors such as the reading materials, parental reading behaviours, the frequency of reading to the child and parental beliefs will contribute to their children's more positive reading habits and outcomes (Greaney and Hegarty, 1987). Subsequently, Mullis et al (2004) suggested that the earlier the parents become involved in their children's literacy practices; the more profound will be the results and more longer-lasting the effects.…”
Section: Developing Reading Environmentsmentioning
confidence: 99%
“…Examining the relationship between parents and children's reading backgrounds and habits, the parental factors such as the reading materials, parental reading behaviours, the frequency of reading to the child and parental beliefs will contribute to their children's more positive reading habits and outcomes (Greaney and Hegarty, 1987). Subsequently, Mullis et al (2004) suggested that the earlier the parents become involved in their children's literacy practices; the more profound will be the results and more longer-lasting the effects.…”
Section: Developing Reading Environmentsmentioning
confidence: 99%
“…Not surprisingly, qualitative and quantitative research studies have shown that children who engage in voluntary reading develop positive attitudes towards reading as an activity (Barbieri, 1995;Greaney, 1980;Greaney & Hegarty, 1987;Hepler & Hickman, 1982;Long & Henderson, 1973;Mathewson, 1994;Reutzel & Hollingsworth, 1991;Shapiro & White, 1991;Short, 1995). This type of reading has also been shown to relate positively to growth in vocabulary, reading comprehension, verbal fluency, and general information (Anderson et al, 1988;Greaney, 1980;Guthrie & Greaney, 1991;Taylor, Frye, & Maruyama, 1990), and to positively correlate with school grades (Anderson et al, 1988;Fielding, Wilson, & Anderson, 1986;Greaney, 1980).…”
Section: The Nature and Importance Of Voluntary Readingmentioning
confidence: 99%
“…In contrast, Pagan and Sénéchal (2009) found not even a significant zero-order correlation between parents' reports of how they currently support literacy at home and third to fifth-grade children's reading motivation (intrinsic, self-concept, and attitude); there was, however, a weak positive correlation (r = .19) between the parent support composite and children's reading activity (measured by frequency of reading for pleasure and author or book title recognition tests). Two other studies involving fifth graders and their parents indicated weak to moderate zero-order correlations of parent support composites with children's amount of leisure reading (Neuman, 1986) and with children's reading attitudes and purpose of reading for enjoyment (Greaney & Hegarty, 1987).…”
Section: Prior Empirical Research On Reading Support Experienced By Omentioning
confidence: 99%
“…The partial correlations employed WJ III Fluency scores as controls. These partial correlations were of interest given that much research indicates that reading achievement and motivation are positively related (e.g., Cunningham & Stanovich, 1997;Guthrie et al, 1999) and some research has shown that reading achievement is related to parent support of older children's reading (e.g., Greaney & Hegarty, 1987;Hansen, 1969). As shown in Table 8, the partial correlations differed very little from the zeroorder correlations.…”
Section: Questionmentioning
confidence: 99%